Effect of non-meat, high protein supplementation on quality of life and clinical outcomes for older people living in care homes: systematic review and meta-analysis - Donaldson, Alison; Smith, Toby O.; Alder, Sarah; Johnstone, Alexandra M.; De Roos, Baukje; Aucott, Lorna S.; Gordon, Adam L.; Myint, Phyo K. (Oxford University Press, 2018)
CONTEXT: Care home residents are at risk of malnutrition through reduced overall food intake, ‘anabolic resistance’ in ageing muscle and high prevalence of medical morbidity and functional dependency. There has been limited consensus regarding effectiveness of a high protein diet on quality of life or clinical outcomes for care home residents.